Ultrathin g-C3N4 with enriched surface carbon vacancies enables highly efficient photocatalytic nitrogen fixation - Zhang, Yi; Di, Jun; Ding, Penghui; Zhao, Junze; Gu, Kaizhi; Chen, Xiaoliu; Yan, Cheng; Yin, Sheng; Xia, Jiexiang; Li, Huaming (Journal of colloid and interface science, 2019)
[Display omitted] An ultra-thin carbon nitride with loose structure and more carbon defects on the surface was achieved through high-temperature peeling methods. Its composition, morphological characteristics, surface defect types and electrochemical properties have been measured. After atomic scale structure control and surface defects construction, the photocatalytic activity of prepared g-C3N4-V for ammonia conversion from dinitrogen can be greatly improved in contrast with bulk g-C3N4. Under visible light irradiation, the defective g-C3N4-V can produce 54 µmol/L NH3 within 100 min without any cocatalyst and sacrificial agent. The relationship between morphology characteristics and activity of defective ultrathin g-C3N4 materials was analyzed in detail. Benefiting from thin layer structure and more surface carbon vacancies, the effective charge separation from both bulk and surface can be achieved. Notably, the engineered carbon vacancies greatly facilitate the adsorption and activation of dinitrogen molecule, extremely improving the nitrogen fixation activity for the defective ultrathin g-C3N4-V materials. This work affords novel insights into the design of photocatalyst with defective ultrathin structure towards nitrogen fixation.